Effectiveness of Community-Based Health Education in Enhancing Dengue Prevention in Remote Areas - Nurul Hidayah; Khaeriah B; Made Dewi Sariyani (Miracle Journal Get Press, 2025)
Dengue fever (DHF) remains a significant public health challenge in remote areas due to limited access to health services and a lack of public awareness regarding disease prevention. This study aimed to assess the role of health education in improving knowledge and behavior related to dengue prevention through a community-based approach. The research used a pretest-posttest design without a control group and applied a quantitative method. A total of 28 participants from high-risk areas were selected using a purposive sampling technique. The health education was delivered through counseling sessions involving lectures, interactive discussions, and visual media such as posters and educational videos. The effectiveness of the health education was evaluated by comparing pretest and posttest scores. The results showed a statistically significant improvement in participants' understanding, with the average score increasing from 54.46 before the health education to 79.36 afterward. This study confirms that interactive and contextualized health education is effective in increasing community awareness and participation in dengue prevention efforts. The findings recommend implementing community-based health education programs tailored to community needs to bridge the information gap and promote sustainable preventive behavior. Further research is recommended to explore the long-term impact and optimization of health education strategies in resource-limited settings.